The improvement of tools for air-abrasive processing in the oral cavity (Literature review) - Mochalov, Юрій Олександрович; Golinka, Ольга Павлівна; Guzo, Нуцу Нуцович; Stupnytska, Олена Миколаївна (Actual Dentistry, 2024)
The purpose of the study is to analyze the content of sources of scientific and medical information related to the development and implementation of air-abrasive processing in dental practice. Materials and methods: an information search was performed in the available electronic databases of scientific and medical information using the relevant keywords “abrasive,” “air-abrasive processing,” “air-flow,” “air-blasting” in the systems “PubMed,” “Scopus” and “Web of Science.” The search depth was 10 years, including secondary sources of information. Results. During the last two decades, air-abrasive treatment in the oral cavity has become almost a standard for professional oral hygiene in dental healthcare institutions in Ukraine. At the time of its creation, this technology involved the use of sodium bicarbonate (soda) powder, which was available in dental practice. In the course of defining the basics of the technology, Robert Black formulated the basic requirements for abrasive materials used in practice. In the absence of accepted manufacturing standards and indicators of such products, the general consensus is a list of requirements for powders for air-abrasive processing: safe removal of dental layers without damage to the enamel surface, no trauma to soft tissues and other structures of the tooth, not to linger in the oral cavity after processing, absence of reaction of a foreign body in case of accidental short-term retention in the patient’s body. Variable influencing factors when performing air-abrasive processing in dentistry remain particle size, pressure in the tip, distance to the treated surface, angle between the surface and the jet, processing time and cutting speed of the jet. The most common substances used as an abrasive component in air-abrasive processing are sodium bicarbonate, calcium carbonate, glycine, and erythritol. Conclusions. Currently, research is ongoing for clinical standardization and development of protocols for air-abrasive treatment in dentistry, improvement of abrasive powder manufacturing technology, and introduction into practice of new substances with high cleaning properties and a minimally invasive effect on tissues and surfaces in the oral cavity. Keywords: dentistry, air-abrasive processing, oral cavity, periodontium, soda, calcium carbonate, glycine, erythritol.